Morbidity profile of cotton mill workers - Yerpude, Pravin N. (Medknow Publications, 2010)
OBJECTIVE: To study the morbidity pattern among cotton mill workers. MATERIAL AND METHODS: This cross-sectional study was conducted in cotton mills in Guntur District (AP) in January 2009 to May 2009. Total 474 workers were included in the study. RESULTS: All study subjects were male. Most of the study subjects belonged to age group 30–40 years (56.96%) and lower socioeconomic status (36.09%) according to modified Kuppuswamy’s classification. The literacy status was varied with 5.70% being illiterate and 37.13% were educated up to primary school. Most of workers were working in Ring frame (41.56%) and majority (58.44%) were working for the last 5–10 years. Mean height of study subjects was 147.42 cm and mean weight was 55.11 kg. The common morbid conditions found were eosinophilia (18.35%), iron deficiency anemia (28.90%), byssinosis grade 1 (7.80%), dental stains (6.54%), refractive errors (7.80%), chronic bronchitis (4.85%), and upper respiratory tract infection (8.64%).